2018
DOI: 10.1073/pnas.1802356115
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic spatial structure of interneuronal correlations in prefrontal microcircuits

Abstract: SignificanceThe spatial structure of correlated activity of neurons in lower-order visual areas has been shown to linearly decrease as a measure of distance. The shape of correlated variability is a defining feature of cortical microcircuits, as it constrains the computational power and diversity of a region. We show here a nonmonotonic spatial structure of functional connectivity in the prefrontal cortex (PFC) where distal interactions are just as strong as proximal interactions during visual engagement of fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 78 publications
(132 reference statements)
2
27
0
Order By: Relevance
“…In canonical cortical microcircuits, horizontal connections allow correlated neural activity. In a region of PFC where visual neurons tuned to object identity (Wilson et al, 1993;Asaad et al, 1998) coexist with genuine hand movement-related cells (Bruni et al, 2015;Simone et al, 2015), the correlated fluctuation of single-neuron activities occurs over long-range distances (Safavi et al, 2018) ( Fig. 2A) compared with the limited-range correlational structure typical of sensory areas, such as V1 (Smith and Sommer, 2013) (Fig.…”
Section: Relevance Of Corticocortical Connections For the Functional mentioning
confidence: 99%
See 1 more Smart Citation
“…In canonical cortical microcircuits, horizontal connections allow correlated neural activity. In a region of PFC where visual neurons tuned to object identity (Wilson et al, 1993;Asaad et al, 1998) coexist with genuine hand movement-related cells (Bruni et al, 2015;Simone et al, 2015), the correlated fluctuation of single-neuron activities occurs over long-range distances (Safavi et al, 2018) ( Fig. 2A) compared with the limited-range correlational structure typical of sensory areas, such as V1 (Smith and Sommer, 2013) (Fig.…”
Section: Relevance Of Corticocortical Connections For the Functional mentioning
confidence: 99%
“…Notice how, at variance from V1 and V4, distal interactions are as strong as proximal interactions during visual stimulation of functionally similar prefrontal neurons. Modified with permission fromSmith and Kohn (2008),Smith and Sommer (2013), andSafavi et al (2018).…”
mentioning
confidence: 99%
“…In the cortex, they drop significantly over distances of 200-400 μm [10,38]. Recent experimental studies have reported correlations varying nonmonotonically with distance [39] or correlations which are positive for closeby neurons but negative for neurons farther apart [40]. Correlation coefficients also depend on the functional properties of the neurons.…”
Section: Introductionmentioning
confidence: 99%
“…(36) and Eq. (38), it is clear that the transformation fromĈ (1) to C (1) mixes elements which are 0 and O( √ K/N ), with those which are O(K/N ). Thus, while inĈ (1) only the elementĈ (1) 12 is O(K/N ), all the elements of the correlation matrix C (1) are O(K/N ).…”
Section: Vi1 Two Population Networkmentioning
confidence: 99%
“…In cortex, they drop significantly over distances of 200 − 400 µm [35,37]. Recent works have reported correlations varying non-monotonically with distance [38] or correlations which are positive for close-by neurons but negative for neurons farther apart [39]. Correlation coefficients also depend on functional properties of the neurons.…”
Section: Introductionmentioning
confidence: 99%